Perspectives on Sámi participation shaping a duty to consult : investigating problem representations and the opportunities to influence policy-making - Andersson, Anna (SLU/Dept. of Urban and Rural Development, 2021)
Sweden has a longstanding reputation internationally for promoting and upholding human rights, however leading up to today the state has repeatedly received critique from international human rights bodies for failing to protect Sámi rights. Therefore the state has initiated the process of developing a duty to consult, which could potentially entail a fundamental change for Sámi rights in Sweden. The development of a policy to strengthen Sámi rights has engaged a wide range of actors and generated an extensive debate. This thesis has examined the divergence in views on this clearly contested issue, and the factors that have held the government back from a law proposal that more fully respects Sámi rights. An application of the WPR approach allowed the study to investigate underlying assumptions and understandings of Sámi participation within the government and among involved actors, and further how these understandings shaped the development of the duty to consult. The findings show that the Swedish state’s aspiration to strengthen Sámi rights falls short, as other interests are valued higher, resulting in a proposed duty to consult that does not fully provide the means for the Sámi people to influence decision-making processes regarding matters that concern them.